Monetary policy in the euro area : strategy and decision making at the European Central Bank - Issing, Otmar (Cambridge University Press, 2001)
How and for whose benefit the European Central Bank (ECB) will work is the most important issue facing Europe. A team from the ECB, including Otmar Issing it's Chief Economist, here present a non-technical analysis of the ECB's monetary policy strategy, institutional features and procedures.